Sugar: Refined Power in a Global Regime - Richardson, B. author. aut Link
X, 244 p. 15 illus.
Keywords: Sugar is a commonplace product with a complex background, mainly because of the high degree of protectionism given to the industry and the benefits of ensuring domestic producers stay in business. This book asks why there are such disagreements over trade policy, who profits within the current regime, and where power ultimately lies.